Trik Menjaga Privacy dan Kenyamanan Anda Ber-Internet (disertai tool-tool praktis) - UTDIRARTATMO, Firrar (Gava Media, 2004)
Trik Menjaga Privacy dan Kenyamanan Anda Ber-Internet (disertai tool-tool praktis)